ANALISIS RASIO KEMANDIRIAN, RASIO EFEKTIVITAS PAD, DAN RASIO EFISIENSI PAD PADA LAPORAN REALISASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) KABUPATEN SUKABUMI - Kartika, Deuis; Kusuma, Indra Cahya (Fakultas Ekonomi Universitas Djuanda, 2015)
This research aims to determine financial performance in autonomous Regency of Sukabumi by analyzing of independency ratio, effectiveness ratio, and local revenue efficiency ratio of PAD on ABPD realization report of Sukabumi Regency. The data used is the budget realization report for fiscal year of 2009-2013. The data analysis usingdescriptive statistical methods. The results showed that financial independency of Sukabumi Regency for fiscal year of 2009-2013 amounted to an average of only 8.15% were classified as very low by showing the pattern of relationships instructive. Local revenue effectiveness ratio of Sukabumi Regency for fiscal year of 2009-2013 average achievement level of 105.67% of the budget set which is classified as very effective. Sukabumi financial performance of 2009-2013 fiscal year by Local Revenue efficiency ratio as very efficient with an average of 5.02% annually.